2015
DOI: 10.1101/gr.183905.114
|View full text |Cite
|
Sign up to set email alerts
|

Origin and domestication of papaya Yh chromosome

Abstract: Sex in papaya is controlled by a pair of nascent sex chromosomes. Females are XX, and two slightly different Y chromosomes distinguish males (XY) and hermaphrodites (XY h ). The hermaphrodite-specific region of the Y h chromosome (HSY) and its X chromosome counterpart were sequenced and analyzed previously. We now report the sequence of the entire male-specific region of the Y (MSY). We used a BAC-by-BAC approach to sequence the MSY and resequence the Y regions of 24 wild males and the Y h regions of 12 cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
113
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 50 publications
3
113
0
1
Order By: Relevance
“…Further evidence is offered by the origin of the Y h chromosome in cultivated hermaphrodite individuals of papaya (VanBuren et al, 2015). By sequencing the entire male-specific region of the Y chromosome and comparing it with the previous sequences of the hermaphrodite-specific region of the Y h chromosome, (Wang et al, 2012), VanBuren et al (2015) found that the Y h chromosome possess lower nucleotide diversity as compared to the Y.…”
Section: Origin and Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further evidence is offered by the origin of the Y h chromosome in cultivated hermaphrodite individuals of papaya (VanBuren et al, 2015). By sequencing the entire male-specific region of the Y chromosome and comparing it with the previous sequences of the hermaphrodite-specific region of the Y h chromosome, (Wang et al, 2012), VanBuren et al (2015) found that the Y h chromosome possess lower nucleotide diversity as compared to the Y.…”
Section: Origin and Distributionmentioning
confidence: 99%
“…Cultivars can inbred, resulting in stable characteristics across generations (Manshardt, 1992). For gynodioecious cultivated papaya, it has been reported that two-thirds of the plants correspond to hermaphrodites and onethird to female plants, though dioecious cultivars exist (VanBuren et al, 2015). Sex determination for the three types of papaya, female, male, and hermaphrodite plants, is genetically regulated by the pairing of sex chromosomes (Carvalho and Renner, 2012), through a sex-linked region that behaves like an XY sex chromosome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…La especie Carica papaya silvestre se encuentra extendida en bosques tropicales que van de México hasta Costa Rica (Chávez-Pesqueira et al, 2014). La versión hermafrodita de C. papaya cultivada es producto de la domesticación por grupos étnicos de México, presumiblemente los mayas (VanBuren et al, 2015).…”
unclassified
“…Carica papaya wild species are widely distributed in tropical forests from Mexico up to Costa Rica (Chávez-Pesqueira et al, 2014). The hermaphrodite version of C. papaya currently sown is the result of domestication by Mexican ethnic groups, presumably the Mayas (VanBuren et al, 2015).…”
mentioning
confidence: 99%